(untitled) (International Journal of Engineering Materials and Manufacture, 2019)
Application of reinforced aluminium scrap for the production of prophylactic knee brace (Pkb) particularly with agro-waste materials is rarely available. In this work, hardness and tensile properties of aluminium alloy (Al 6063) straps reinforced with cow bone (Cb) and periwinkle shell (Ps) for the production of Pkb were investigated. The Cb and Ps sourced were cleaned and the Cb was sun-dried for 4 weeks before crushing with Denver laboratory Ball mill (Model: 48-D0500/Q). The Ps was also crushed, sun-dried for 7 days and treated in the oven (Model SDO/225) at 110 oC for 30 minutes to remove moisture. The particle size of 75 Âµm was used to cast six (6) each of aluminium/cowbone (Al/Cb) and aluminium/periwinkle shell (Al/Ps) composites. The cast aluminium composites of Pkb and original Pkb were investigated for density, hardness, and tensile properties. It was observed that addition of Cb and Ps in the cast Pkb gave a density of 2.68 g/cm3 and 2.60 g/cm3 respectively. The average values of hardness and tensile strength obtained were 41.18 BHN and 135.88 MPa respectively when Ps was added to the cast aluminium Pkb, while addition of Cb gave harness values of 40.45 BHN and tensile strength of 134.63 MPa.